ISLAMIC PERSPECTIVES ON ENVIRONMENTAL CONSERVATION AND GOVERNMENT POLICIES ON MITIGATING THE NATURAL DISASTER IN INDONESIA - Putra, Dedisyah; Hasibuan, Zuhdi; Edi, Sabrun (State Islamic University North Sumatra, 2023)
Abstract: This article will find policy considerations in disaster mitigation planning by looking at disasters that have occurred before and Islam contributes to caring for the environment before, during and after disasters. This research uses a qualitative approach with a literature study method. Data were obtained from secondary sources to explore conceptual and comparative perspectives. The results of this study are three, namely; Islamic teachings in the Qur'an and Hadith show guidelines for humans to preserve nature to prevent natural disasters early on. Government policy also plays an important role in preventing all possibilities that have the potential to trigger natural disasters. Finally, two factors, namely Islamic teachings and government policies in terms of preventing disasters, must create the prevention of natural disasters.Keywords: Environment, Conservation, Islam, Indonesian policy, Mitigating